PENGARUH ETIKA KERJA, TANGGUNG JAWAB SOSIAL, DAN REPUTASI TERHADAP KUALITAS LAYANAN KARYAWAN KESYAHBANDARAAN DAN OTORITAS PELABUHAN UTAMA MAKASSAR - Ramadhan, Gilang; Yusuf, Muhammad; Nasrullah, Nasrullah (Universitas Teuku Umar, 2025)
This study aims to determine the influence of Work Ethics, Social Responsibility, and Reputation on the Service Quality of employees at the Main Office of Kesyahbandaran and Port Authority Makassar. This research uses a quantitative approach with a total of 75 respondents. Data collection methods included observation, documentation, and questionnaire distribution. Data were analyzed using multiple linear regression tests and hypothesis testing with t-tests. The results showed that work ethics, social responsibility, and reputation have a positive and significant effect on service quality. This study indicates that these variables collectively play an important role in shaping excellent service quality within the Kesyahbandaran and Port Authority Makassar environment. Keywords : Work Ethics, Social Responsibility, Reputation, Service Quality.